Competencies and Entrustable Professional Activities: new models for elaboration of a Curriculum Framework for Family and Community Medicine Residency - Borges Costa, Lourrany (2018)
Objective: The purpose is to carry out a literature review on Competency Based Curriculum that could support the elaboration of a matrix for the Residency Program in Family and Community Medicine of Fortaleza, Ceará. Methods: A literature review was made on the theoretical reference of competency-based education, selecting articles, guidelines, documents and curricula models of medical schools and national and international entities involved with medical education. Results: The literature review evidenced two main curriculum models repeatedly mentioned in the references: ACGME (Accreditation Council for Graduate Medical Education) Milestones and CanMEDS (Canadian Medical Education Directions for Specialists) Framework. Competency-Based Curriculum emphasizes student-centered teaching and uses a results-based approach to the design, implementation, and evaluation of medical education programs. It is organized as a framework of competencies mapped to entrustable professional activities in the form of a matrix. The evaluation is based on performance through milestones. For creating its own curricular Matrix, the CanMEDS 2015 was adopted as a model because it was approved by 12 Canadian medical organizations and it is currently used as reference in dozens of countries, being the most widely applied model in the world. Conclusion: We expect that this review would serve as a tool for other Medical Schools and their Residency Programs to develop their own Competency-Based Curricula.